Peripheral Giant Cell Granuloma Associated with a Dental Implant: A Case Report and Review of the Literature - Amy Louise Brown; Paulo Camargo de Moraes; Marcelo Sperandio; Andresa Borges Soares; Vera Cavalcanti Araújo; Fabrício Passador-Santos (Case Reports in Dentistry)
The peripheral giant cell granuloma (PGCG) is a nonneoplastic lesion commonly caused by local irritation. This report describes a 46-year-old Caucasian male who presented with a PGCG associated with a dental implant. The dental implant was originally placed in August 2012. Ten months later, the patient presented with a well-circumscribed lesion associated with and covering the implant, at which time the lesion was excised. Four months later, due to recurrence of the lesion, a deeper and wider excisional biopsy with curettage of the adjacent bone was performed. No evidence of recurrence has been reported after 12 months of follow-up. Immunohistochemistry, using the antibody CD68, was performed to investigate the origin of the multinucleated giant cells, with their immunophenotype being similar to those of other giant cell lesions, including central giant cell granuloma, foreign-body reactions, and granulomatous reactions to infectious agents.